Multidisciplinary studies in Cucurbita maxima (squash) domestication - Martínez, Analía Beatriz Luján (2017)
Plant domestication is a complex process in which natural and cultural factors play important roles delimiting evolutionary pathways of plants under cultivation. In order to deal with and understand the changes generated during this process, multi-disciplinary research is required, especially when a full picture of the domestication history of a taxon is to be assessed. We present here some advances in the study of Cucurbita maxima (squash) domestication from an integrated perspective, including experimental, morphometric and archaeobotanical approaches, which are discussed in the light of new data from physiological analyses. Modern material includes plants obtained from experimental fields, derived from crosses between domesticated (C. maxima ssp. maxima) and spontaneous/wild forms (C. maxima ssp. andreana), resulting in F1 and F2 generations. The archaeobotanical material includes remains recovered from sites in southern Peru and northwest Argentina ranging in date from 3,000 to 800 bp. Morphological and anatomical analyses were conducted on seeds, pericarps and peduncles (the stem of the flower or fruit) for reconstructing squash size and shape evolution under domestication. The results suggest the presence of hybrid forms, mainly from the earlier sites, but also from more recent ones. As expected, a linear evolutionary pathway was not found. Diversity and multiple crossings seem to have been a constant in squash cultivation over time, emphasising the role of gene flows between domestic and wild variants in the domestication process. Finally, we hypothesize the possible linkage between past gene flow and different dormancy patterns as part of management practices, allowing the maintenance of squash populations adapted to different environmental conditions.